2022
DOI: 10.1111/jam.15469
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and molecular characterization of ESBL-producing and colistin-resistant Escherichia coli isolates recovered from healthy food-producing animals in Pakistan

Abstract: Objectives: To investigate the occurrence and molecular features of ESBL-producing and colistin-resistant Escherichia coli isolates recovered from healthy food-producing animals in Pakistan. Methods: A total of 153 E. coli isolates were recovered from 250 faecal samples collected from livestock and poultry. The antibiotic susceptibility, resistant determinants and mobile genetic elements were determined for all the isolates. The clonal relatedness was analysed by MLST. Plasmids harbouring, localization and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
(73 reference statements)
0
12
0
Order By: Relevance
“…In Table 1 , Table 2 and Table 3 , the pattern of sensibility in the 5306 in this study is represented. The isolates presented higher resistance percentages to erythromycin (54.7%), ampicillin (50.9%), and penicillin (49.6%) of all the tested antibiotics [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Table 1 , Table 2 and Table 3 , the pattern of sensibility in the 5306 in this study is represented. The isolates presented higher resistance percentages to erythromycin (54.7%), ampicillin (50.9%), and penicillin (49.6%) of all the tested antibiotics [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is a startling discovery, as until now, sheep-origin E. coli resistance has been neglected. Recent studies have confirmed the presence of MDR ESBL-producing E. coli in sheep in Pakistan, Chile, Brazil, Portugal, and the United States ( 24 28 ). To the best of our knowledge, this is the first report of the multidrug resistance determinants of ESBL-producing E. coli isolates of sheep origin in China.…”
Section: Discussionmentioning
confidence: 90%
“…A sterilized 0.45 μm microporous filter membrane was applied to MH medium, and the mixture was spread onto the membrane. After culturing at 37°C for 12 h, transconjugants were selected on MacConkey agar containing 4 mg/L colistin and 200 mg/L sodium azide and confirmed using enterobacterial repetitive intergenic consensus (ERIC)-PCR and PCR analysis of mcr-1 ( Liu et al, 2020 ; Shafiq et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%